Respostas

2014-07-24T11:22:48-03:00
A) x²-4x-12=0
Δ= 16+48
Δ=64
x'=4+8 = 12 = 6 
     2       2
x"=4-8 = -4 = -2
      2      2

b) 2x² +5x +3 = 0
    Δ=25-24
    Δ= 1
    x'= -5+1 = -4 = -1
            4       4

    x"= -5-1 = -6 = -3
            4       4     2
 
1 5 1
obrigado ajudo muito
a letra b sua esta errada vc pois - 6/2 mas era - 6/4 = - 3/2
eu não copiei essa letra b mesmo
2014-07-24T11:44:35-03:00
A) x² - 4x - 12 = 0
Delta = (- 4)^2 - 4.1.(- 12)
Delta = 16 + 48
Delta = 64

x = 4 + - raiz de 64 / 2
x = 4 + - 8 / 2

x' = 4 + 8 / 2 = 12 / 2 = 6

x" = 4 - 8 / 2 = - 4 / 2 = - 2

b)2x^2 + 5x^2 + 3 = 0
7x^2 + 3 = 0
7x^2 = - 3
x^2 = - 3 / 7
x = + - raiz de - 3 / 7

b) 2x^2 + 5x + 3 = 0
Delta = (5)^2 - 4.2.3
Delta = 25 - 24
Delta = 1

x = - 5 + - raiz de 1 / 4
x = - 5 + - 1 / 4

x' = - 5 + 1 / 4 = - 4 / 4 = - 1

x " = - 5 - 1 / 4 = - 6 / 4 = - 3 / 2